Elotuzumab plus lenalidomide and dexamethasone in relapsed/refractory multiple myeloma: Extended 3‐year follow‐up of a multicenter, retrospective clinical experience with 319 cases outside of controlled clinical trials. Issue 4 (1st June 2022) - Bruzzese, Antonella; Derudas, Daniele; Galli, Monica; Martino, Enrica Antonia; Rocco, Stefano; Conticello, Concetta; Califano, Catello; Giuliani, Nicola; Mangiacavalli, Silvia; Farina, Giuliana; Lombardo, Alessandra; Brunori, Marino; et al.
Abstract: The combination of elotuzumab, lenalidomide, and dexamethasone (EloRd) enhanced the clinical benefit over Rd with a manageable toxicity profile in the ELOQUENT‐2 trial, leading to its approval in relapsed/refractory multiple myeloma (RRMM). The present study is a 3‐year follow‐up update of a previously published Italian real‐life RRMM cohort of patients treated with EloRd. This revised analysis entered 319 RRMM patients accrued in 41 Italian centers. After a median follow‐up of 36 months (range 6–55), 236 patients experienced disease progression or died. Median progression‐free survival (PFS) and overall survival (OS) were 18.4 and 34 months, respectively. The updated multivariate analyses showed a significant reduction of PFS and OS benefit magnitude only in cases with International Staging System stage III. Major adverse events included grade 3/4 neutropenia (18.5%), anemia (15.4%), lymphocytopenia (12.5%), and thrombocytopenia (10.7%), while infection rates and pneumonia were 33.9% and 18.9%, respectively. No new safety signals with longer follow‐up have been observed. Of 319 patients, 245 (76.7%) reached at least a partial remission. A significantly lower response rate was found in patients previously exposed to lenalidomide. In conclusion, our study confirms that EloRd is a safe and effective regimen for RRMM patients, maintaining benefits across multiple unfavorable subgroups.